School of Management, Marketing and Commerce Studies - R. B. Nozdryova (Vestnik MGIMO-Universiteta)
Governance and regulation at the national and international level, the management system of the leading companies in the world, forms and methods of management, and marketing, commercial and advertising work form a relatively new subject field in domestic science. These issues have been introduced into the educational process in Russian universities in the second half of the 1980s. At the MGIMO these research areas have been developed for more than 60 years. Scientific School of the Department of Management and Marketing and the Department of Management Foreign Economic Activity is oriented at the international level and focuses on the development of organizational forms and methods of management, marketing strategy, marketing, and commerce in the context of foreign trade and international activities of domestic firms and organizations on the basis of a comprehensive study of advanced management experience of leading foreign countries. In the early stages of its existence, the school was focused on methodological and practical aspects of international commerce and advertising. But gradually its research encompassed the field of management and marketing, and the scientific school in the field of international management and marketing was established on the basis of examination of relevant theories and experiences of leading foreign countries, and especially multinational companies. Originally these studies were conducted by the Department International Economic Relations of the Faculty of International Economic Relations at MGIMO. The disciplines included studies of the foreign trade operations in global markets, management of foreign economic activities in foreign countries, world commodity markets, and others. The textbook "Organization and technology of foreign trade in the capitalist market" by I.N. Gerchikova, Honored Scientist of the Russian Federation, Doctor of Economic Science, Professor, published in 1977 already contained sections on management and marketing, including the organizational structure of firms and their international marketing work, international advertising, etc. PhD. Professor F.G. Piskoppel, Ph.D. Professor S.P. Nikitin systematically analyzed forms and methods of market research, which are an integral part of the marketing activities of companies in global markets.